Extra-nuclear starbursts: Young luminous hinge clumps in interacting galaxies - Smith, B.; Soria, Roberto; Struck, C.; Giroux, M.; Swartz, D.; Yukita, M. (Institute of Physics Publishing, Inc, 2014)
Hinge clumps are luminous knots of star formation near the base of tidal features in some interacting galaxies. We use archival Hubble Space Telescope (HST) UV/optical/IR images and Chandra X-ray maps along with Galaxy Evolution Explorer UV, Spitzer IR, and ground-based optical/near-IR images to investigate the star forming properties in a sample of 12 hinge clumps in five interacting galaxies. The most extreme of these hinge clumps have star formation rates of 1-9 M ☉ yr–1, comparable to or larger than the "overlap" region of intense star formation between the two disks of the colliding galaxy system the Antennae. In the HST images, we have found remarkably large and luminous sources at the centers of these hinge clumps. These objects are much larger and more luminous than typical "super star clusters" in interacting galaxies, and are sometimes embedded in a linear ridge of fainter star clusters, consistent with star formation along a narrow caustic. These central sources have FWHM diameters of ~70 pc, compared to ~3 pc in "ordinary" super star clusters. Their absolute I magnitudes range from MI ~ – 12.2 to –16.5; thus, if they are individual star clusters they would lie near the top of the "super star cluster" luminosity function of star clusters. These sources may not be individual star clusters, but instead may be tightly packed groups of clusters that are blended together in the HST images.Comparison to population synthesis modeling indicates that the hinge clumps contain a range of stellar ages. This is consistent with expectations based on models of galaxy interactions, which suggest that star formation may be prolonged in these regions.In the Chandra images, we have found strong X-ray emission from several of these hinge clumps. In most cases, this emission is well-resolved with Chandra and has a thermal X-ray spectrum, thus it is likely due to hot gas associated with the star formation. The ratio of the extinction-corrected diffuse X-ray luminosity to the mechanical energy rate (the X-ray production efficiency) for the hinge clumps is similar to that in the Antennae galaxies, but higher than those for regions in the normal spiral galaxy NGC 2403. Two of the hinge clumps have point-like X-ray emission much brighter than expected for hot gas; these sources are likely "ultra-luminous X-ray sources" due to accretion disks around black holes. The most extreme of these sources, in Arp 240, has a hard X-ray spectrum and an absorbed X-ray luminosity of ~2 × 1041 erg s–1; this is above the luminosity expected by single high mass X-ray binaries (HMXBs), thus it may be either a collection of HMXBs or an intermediate mass black hole (≥80 M ☉).